MODERN MANAGEMENT OF ACUTE RESPIRATORY INFECTIONS IN CHILDREN. RECOURSES OF SYSTEM ANTI INFLAMMATORY TREATMENT - O.V. Zaitseva ("Paediatrician" Publishers LLC, 2008)
A problem of etiology and pathogenesis of acute respiratory infections in children are observed in this article. Modern approach to management of its treatment in pediatric patients, including often ailing children, is described. Authors give characteristics to main directions of treatment of obstructive syndrome. An experience of anti-inflammatory therapy with fenspiride (eurespal) in children of different age is summa ized in this article.Key words: often ailing children, acute respiratory infections, bronchoobstructive syndrome, anti-inflammatory treatment, fenspiride.